Associations between air pollution and psychiatric symptoms in the Normative Aging Study - Xinye Qiu; Mahdieh Danesh-Yazdi; Marc Weisskopf; Anna Kosheleva; Avron Spiro; Cuicui Wang; Brent A Coull; Petros Koutrakis; Joel D Schwartz (Environmental Research Letters, 2022)
Environmental risk factors for psychiatric health are poorly identified. We examined the association between air pollution and psychiatric symptoms, which are often precursors to the development of psychiatric disorders. This study included 570 participants in the US Veterans Administration (VA) Normative Aging Study (NAS) and 1114 visits (defined as an onsite follow-up at the VA with physical examination and questionnaires) from 2000 to 2014 with information on the brief symptom inventory (BSI) to assess their psychiatric symptom levels. Differences in the three BSI global measures (global severity index (GSI), positive symptom distress index (PSDI) and positive symptom total (PST)) were reported per interquartile (IQR) increase of residential address-specific air pollutants levels (fine particulate matter—PM _2.5 , ozone—O _3 , nitrogen dioxide—NO _2 ) at averages of one week, four weeks, eight weeks and one year prior to the visit, using generalized additive mixed effects models. We also evaluated modification by neighborhood factors. On average, among the NAS sample (average age: 72.4 years (standard deviation: 6.7 years)), an IQR increase in one and four week averages of NO _2 before a visit was associated with a PSDI T score (indicator for psychiatric symptom intensity) increase of 1.60 (95% confidence interval (CI): 0.31, 2.89), 1.71 (95% CI: 0.18, 3.23), respectively. Similarly, for each IQR increase in one and four week averages of ozone before a visit, the PSDI T -score increased by 1.66 (95% CI: 0.68, 2.65), and 1.36 (95% CI: 0.23, 2.49), respectively. Stronger associations were observed for ozone and PSDI in low house-value and low household income areas. No associations were found for PM _2.5 . Exposure to gaseous air pollutants was associated with a higher intensity of psychiatric symptoms among a cohort of older men, particularly in communities with lower socio-economic or housing conditions.